The Improving Teenage Athlete Sports Motivation Through Identity Awareness Training - Sekar Widyaningrum Ramadhani; Miftakhul Jannah (Character Jurnal Penelitian Psikologi, 2023)
Identity awareness trainingis a self-awareness learning model through the provision of material, discussion, and completing games. The purpose of this training is to obtain a description of the application of identity awareness training to the sports motivation of young athletes, and to increase the motivation of young athletes through identity awareness training. The method used in this research is quantitative experiment. The sampling technique is saturated sampling. Data collection was carried out by distributing exercise motivation scale questionnaires. This questionnaire is presented in the form of a Google form with hypothesis testing using SPSS version 26.00 for windows. The results of this study showthe significant value in the experimental group was 0.009 so it was less than 0.05 meaning that there was a significant difference in the pretest and posttest in the experimental group. And the significant value in the control group was 0.448 so that it was greater than 0.05 meaning that there was no significant difference in the pretest and posttest in the control group. The results of the analysis above, it was concluded that identity awareness training has an influence on sports motivation.